Relasi Pemikiran Nabia Abbott dan Ignaz Goldziher dalam Studi á¸¤adÄ«th - Muawanah, Arofatul (Fakultas Ushuluddin, Adab dan Humaniora Institut Agama Islam Negeri (IAIN) Jember, 2017)
Among the Orientalists, who have different ideas, are Ignaz Goldziher and Nabia Abbott. In his study, Goldziher always show a sharp criticism of the scientific construction of á¸¥adÄ«th and his views on á¸¥adÄ«th have been always dissimilar with scholars of á¸¥adÄ«th. He also alleges that the existence of á¸¥adÄ«th is no longer original. Abbottâ€™s thought of á¸¥adÄ«th, in contrast, tends to be moderate. Broadly speaking, Abbottâ€™s views seem to reinforce the thought of â€˜ulamÄâ€™ al-á¸¥adÄ«th. Abbott even acknowledges that the compilation of á¸¥adÄ«th has existed since the Prophet Muhammadâ€™s lifetime. In this context, it is interesting to note that Goldziher and Abbott are equally orientalists who employ the Western paradigm in examining á¸¥adÄ«th. The question is whether there is a relationship of thought between the two. Using descriptive and analytical methods this article specifically traces and explores the relationship of Abbott and Goldziherâ€™s thoughts. The study aims to determine the extent to which the relation of thought between the two Orientalists and the factors affect the similarity of thought between them.